2013
DOI: 10.1128/jvi.02257-12
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Seasonal H1N1 Influenza Virus Infections Protect Ferrets against Novel 2009 H1N1 Influenza Virus

Abstract: d Individuals <60 years of age had the lowest incidence of infection, with ϳ25% of these people having preexisting, cross-reactive antibodies to novel 2009 H1N1 influenza. Many people >60 years old also had preexisting antibodies to novel H1N1. These observations are puzzling because the seasonal H1N1 viruses circulating during the last 60 years were not antigenically similar to novel H1N1. We therefore hypothesized that a sequence of exposures to antigenically different seasonal H1N1 viruses can elicit an ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
77
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(92 citation statements)
references
References 39 publications
12
77
1
Order By: Relevance
“…We recently showed that of the individuals .45 y of age with undetectable HI titers to A(H1N1) pdm09, nearly all (28/31, 90%) had ADCC-mediating Abs to the A(H1N1)pdm09 virus prior to the 2009 pandemic (44). Numerous animal studies showed that infection with seasonal H1N1 viruses, particularly with H1N1 viruses circulating pre-1960, can provide a level of protection from severe A (H1N1)pdm09 virus infection (21,(60)(61)(62)(63). In studies in which Nabs against A(H1N1)pdm09 could not be detected, the levels of nonneutralizing binding Abs correlated closely with protection from severe A(H1N1)pdm09 infection (12,61).…”
Section: The Influence Of Influenza Adcc-mediating Abs On the 2009 Pamentioning
confidence: 99%
“…We recently showed that of the individuals .45 y of age with undetectable HI titers to A(H1N1) pdm09, nearly all (28/31, 90%) had ADCC-mediating Abs to the A(H1N1)pdm09 virus prior to the 2009 pandemic (44). Numerous animal studies showed that infection with seasonal H1N1 viruses, particularly with H1N1 viruses circulating pre-1960, can provide a level of protection from severe A (H1N1)pdm09 virus infection (21,(60)(61)(62)(63). In studies in which Nabs against A(H1N1)pdm09 could not be detected, the levels of nonneutralizing binding Abs correlated closely with protection from severe A(H1N1)pdm09 infection (12,61).…”
Section: The Influence Of Influenza Adcc-mediating Abs On the 2009 Pamentioning
confidence: 99%
“…When comparing maximal amino acid distances between AMA1 and influenza H1 HA (Figures 2 and 3), it is evident that influenza HA is more variable than AMA1 [41,[43][44][45]. Huber et al have shown that a prime with DNA followed by a live-attenuated virus boost with a mixture of three H3N2 viruses (Hong Kong 1968, Victoria 1975, and Leningrad 1986) covers 20 years of antigenic drift in mice [43].…”
Section: Edip For Influenzamentioning
confidence: 99%
“…Huber et al have shown that a prime with DNA followed by a live-attenuated virus boost with a mixture of three H3N2 viruses (Hong Kong 1968, Victoria 1975, and Leningrad 1986) covers 20 years of antigenic drift in mice [43]. Carter et al show that sequential infection in ferrets with three seasonal H1N1 strains (either historical or modern) confers protection against H1N1pdm challenge (not contained in infection series) [41]. Moreover, a mixture of sera obtained after infection with single viruses neutralized H1N1pdm, while none of the separate sera had neutralizing activity [41].…”
Section: Edip For Influenzamentioning
confidence: 99%
See 2 more Smart Citations